Effect of iodine doping on the characteristics of polythiophene thin films prepared by aerosol assisted plasma jet polymerization at atmospheric pressure - Abdullah, Manal Midhat (Iraqi Journal of Physics, 2019)
Iodine-doped polythiophene thin films are prepared by aerosol assisted plasma jet polymerization at atmospheric pressure and room temperature. The doping of iodine was carried out in situ by employing iodine crystals in thiophene monomer by weight mixing ratios of 1%, 3%, 5% and 7%. The chemical composition analyses of pure and iodine-doped and heat-treated polythiophene thin films are carried out by FTIR spectroscopy studies. The optical band gaps of the films are evaluated from absorption spectrum studies. Direct transition energy gaps are determined from Tauc plots. The structural changes of polythiophene upon doping and the reduction of optical band gap are explained on the basis of the results obtained from FTIR spectroscopy, UV–VIS absorption studies, X-ray diffraction and atomic force microscope (AFM) analysis. The energy band gap will be different according to the concentration of polythiophene iodine. It can be concluded that iodine-doped polythiophene thin films can be prepare by aerosol assisted plasma jet polymerization and control the optical energy band gap regulars by controlling the thiophene -iodine weight mixing ratios.